Adaptive hybrid methods for improving the quality of ultrasonic images of skin - LEWANDOWSKI, M.; NOWICKI, A. (Archives of Acoustics, 1998)
This study is concerned with methods for improving the quality of micro-ultrasonographic images using digital signal processing. A method of linear adaptive filtering is presented, which makes it possible to reduce speckle in ultrasonographic images, and its non-linear modification is proposed. Quantitative results of one-dimensional simulation of these filters is proposed and the results for real micro-ultrasonographic images of skin are presented.